The Effectiveness and Valuation of Using Silt Pit to Reduce Erosion and Nutrient Loss of Andosol - Masnang, Andi; Jannah, Asmanur; Andriyanty, Reny; Haryati, Umi (JOURNAL OF TROPICAL SOILS, 2022)
The silt pit is a method of soil management that functions to accommodate and absorb surface runoff. The research aimed to determine the silt pit effectiveness for erosion reduction and nutrient loss. The research is located at 576 above sea level (asl) in Sukamantri village, Taman Sari district, Bogor Regency. The experiment used a randomized block design with three replications and a slope group. The treatments were R0 (without silt pit); R1 (silt pit); R2 (silt pit + mulch); R3 (silt pit + mulch + biopore tube), R4 (silt pit + mulch + biopore tube + vertical crop tube). The highest runoff-decreasing occurred on R4 treatment, which pressed down 29.38% runoff. The highest value of erosion-decreasing occurred on R2 as 68.74% and followed by effectiveness in reducing the loss of 71% Organic C, 76% available P, and 67% total N. The dry seeds peanut yield was around 0.54 - 0.86 Mg ha-1, dried pods was 0.96 - 1.33 Mg ha-1, and dried biomass was 5.16 - 6.23 Mg ha-1 and not significantly different between all treatments. This study recommends that farmers apply silt pit innovation technology with a combination of mulch, biopore, and mature green media because the incremental B/C ratio was 1.175. It is a good economic indicator for farmers.